TANGGAPAN RESPONDEN MENGENAI GAME BATTLE KANJI SEBAGAI MEDIA ALTERNATIF PEMBELAJARAN KANJI TINGKAT DASAR - Heri Ahmadi; Anisa Arianingsih; Renariah Renariah (Janaru Saja: Jurnal Program Studi Sastra Jepang (Edisi Elektronik), 2019)
This study discusses the responses of respondents about the game "Battle Kanji". The method used is ADDIE. The data were taken through from a questionnaire given to 17 students from the Japanese Literature Study Program of UNIKOM academic year 2018/2019. The results showed that the respondents agreed with the "Battle Kanji" as an alternative media to learn kanji basic level with an attractive appearance, content that is easy to understand, and easy operation with 83,7% percentage value. This study is expected by the growing number of researchers to create media that can make it easier and more engaging learners in learning Japanese kanji, especially at a basic level. Keywords: Alternative Media, ADDIE, Battle Kanji, Game